2020
DOI: 10.1109/ojemb.2020.3030531
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Non-1H RF Receive Arrays in Magnetic Resonance Imaging and Spectroscopy

Abstract: It is now common practice to use radiofrequency (RF) array coils to increase the signal-to-noise ratio (SNR) in 1 H magnetic resonance imaging and spectroscopy experiments. Use of array coils for non-1 H experiments, however, has been historically more limited despite the fact that these nuclei suffer inherently lower sensitivity and could benefit greatly from an increased SNR. Recent advancements in receiver technology and increased support from scanner manufacturers have now opened greater options for the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 129 publications
(224 reference statements)
0
3
0
Order By: Relevance
“…40 Use of array coils is an attractive approach in sodium imaging to further increase the SNR and reduce scan time by using parallel imaging strategies. 41 For example, Lee et al 42 demonstrated up to a 400% increases in the SNR using a 4-channel coil .20 years ago. To date, the highest number of channels reported for a head sodium coil is 32, 28 while 20-to 30-channel coils are commercialized and available through third-party coil vendors.…”
Section: Sodium Mr Imaging Physics and Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Use of array coils is an attractive approach in sodium imaging to further increase the SNR and reduce scan time by using parallel imaging strategies. 41 For example, Lee et al 42 demonstrated up to a 400% increases in the SNR using a 4-channel coil .20 years ago. To date, the highest number of channels reported for a head sodium coil is 32, 28 while 20-to 30-channel coils are commercialized and available through third-party coil vendors.…”
Section: Sodium Mr Imaging Physics and Acquisitionmentioning
confidence: 99%
“…However, despite remarkable progress, array coils are still rarely used in sodium imaging because of hardware and software limitations and additional costs. 41 For using array coils in sodium MR imaging, the receivers should be capable of handling the frequencies relevant to sodium acquired with analog-to-digital converters and having processing engines capable of sorting and combining the signals from each coil properly. Most commercial scanners have offered only a single broadband X-nuclei receiver channel, limiting the use of array coils.…”
Section: Sodium Mr Imaging Physics and Acquisitionmentioning
confidence: 99%
“…Phased arrays 34 are nowadays widely used for signal reception because of their ability to reduce sample noise and yield high SNR on surfaces and deeper inside objects 35 and to enable image acceleration through parallel imaging. 36 Phased arrays have been developed for imaging 1 H 37 and nonproton nuclei 38 like 13 C 39 and 31 P 40 . However, experiments with cryogenic coil arrays are sparse.…”
Section: Introductionmentioning
confidence: 99%